Eneolithic copper smelting slags in the Eastern Alps: Local patterns of metallurgical exploitation in the Copper Age. (November 2015) - Artioli, G.; Angelini, I.; Tecchiati, U.; Pedrotti, A.
Abstract: A number of slags of all known sites in the Italian Eastern Alps showing occurrences of copper smelting activities in the Copper Age have been characterized by lead isotope analysis. All the investigated smelting slags from Trentino (Romagnano Loc, La Vela, Gaban, Acquaviva di Besenello, Montesei di Serso) and Alto Adige/Sud Tyrol (Millan, Gudon, Bressanone Circonvallazione Ovest) have been recently characterized by thorough mineralogical, petrographical and chemical analysis and demonstrated to be the product of copper smelting activities of chalcopyrite-based mineral charges, with an immature technological extraction process referred as the "Chalcolithic" smelting process. Revision of the available radiocarbon dates show that the metallurgical activities pertaining to the analysed slags can be attributed to the third millennium BC. The lead isotope analysis indicates clearly that the mineral charge use for the smelting process was extracted from nearby mineral deposits. The detailed analysis of the spatial distribution of ores and slags allows for the first time to define the local organization of the metallurgical operations. Highlights: Eneolithic copper smelting slags from the South-Eastern Alps were analysed for Pb isotopes. The ore provenance based on the AAcP database reveals the mine exploitation patterns. The isotopic affinity of slags and coeval objects points to an extensive Alpine copper production.